Electroacupuncture improves gout arthritis pain via attenuating ROS-mediated NLRP3 inflammasome overactivation - Huina Wei; Boyu Liu; Chengyu Yin; Danyi Zeng; Huimin Nie; Yuanyuan Li; Yan Tai; Xiaofen He; Boyi Liu (BMC, 2023)
Abstract Background Gout results from disturbed uric acid metabolism, which causes urate crystal deposition in joints and surrounding tissues. Gout pain management is largely limited to colchicine and nonsteroidal anti-inflammatory drugs. Constant usage of these medications leads to severe side effects. We previously showed electroacupuncture (EA) is effective for relieving pain in animal model of gout arthritis. Here we continued to study the mechanisms underlying how EA alleviates gout pain. Methods Monosodium urate was injected into ankle joint to establish gout arthritis model in mice. EA or sham EA was applied at ST36 and BL60 acupoints of model animals. Biochemical assays, immunostaining, live cell Ca2+ imaging and behavioral assays were applied. Results Model mice displayed obvious mechanical allodynia, accompanied with gait impairments. EA attenuated mechanical hypersensitivities and improved gait impairments. EA reduced the overexpression of NLRP3 inflammasome signaling molecules in ankle joints of model animals. EA-induced anti-allodynia, as well as inhibition on NLRP3 inflammasome, were mimicked by antagonizing but abolished by activating NLRP3 inflammasome via pharmacological methods. EA attenuated oxidative stress, an upstream signaling of NLRP3 inflammasome in ankle joints of model mice. Exogenously increasing oxidative stress abolished EA's inhibitory effect on NLRP3 inflammasome and further reversed EA's anti-allodynic effect. EA reduced neutrophil infiltrations in ankle joint synovium, a major mechanism contributing to oxidative stress in gout. Pharmacological blocking NLRP3 inflammasome or EA reduced TRPV1 channel overexpression in dorsal root ganglion (DRG) neurons. Ca2+ imaging confirmed that EA could reduce functional enhancement in TRPV1 channel in DRG neurons during gout. Conclusions Our results demonstrate that EA reduces gout pain possibly through suppressing ROS-mediated NLRP3 inflammasome activation in inflamed ankle joints and TRPV1 upregulation in sensory neurons, supporting EA as a treatment option for gout pain.